2013
DOI: 10.4331/wjbc.v4.i4.111
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive and maladaptive expression of the Mrna regulatory protein HuR

Abstract: The RNA-binding proteins involved in regulation of mRNA post-transcriptional processing and translation control the fates of thousands of mRNA transcripts and basic cellular processes. The best studied of these, HuR, is well characterized as a mediator of mRNA stability and translation, and more recently, as a factor in nuclear functions such as pre-mRNA splicing. Due to HuR's role in regulating thousands of mRNA transcripts, including those for other RNA-binding proteins, HuR can act as a master regulator of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 70 publications
3
39
0
Order By: Relevance
“…A moderate level of HuR expression is required for cell survival, since its absence results in cell death [55]. Yet, its overexpression is well-established to play a role in oncogenic transformation and tumor invasiveness [11, 12, 22, 29, 45, 56-64]. Therefore, even under conditions of cell stress, when normal translational regulation may be impaired, it is critical that HuR expression is maintained at appropriate levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A moderate level of HuR expression is required for cell survival, since its absence results in cell death [55]. Yet, its overexpression is well-established to play a role in oncogenic transformation and tumor invasiveness [11, 12, 22, 29, 45, 56-64]. Therefore, even under conditions of cell stress, when normal translational regulation may be impaired, it is critical that HuR expression is maintained at appropriate levels.…”
Section: Discussionmentioning
confidence: 99%
“…Because HuR function must be finely tuned to create a balance between cell proliferation and survival on one hand, and oncogenic transformation on the other, its expression is tightly controlled at multiple levels [12]. At a post-transcriptional level, HuR mRNA levels are controlled by multiple regulators of mRNA stability [13, 14], including HuR itself, since its expression may be autoregulated [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…HuR is located into the nucleus and, in response to stimuli, can shuttle to the cytoplasm to allow its mRNA target to be processed. Several studies demonstrated that HuR is overexpressed and delocalized in the cytoplasm in numerous cancers, including breast cancer, lung adenocarcinoma, ovarian cancer, laryngeal squamous cell cancer and colon cancer (6,7). Moreover, various mRNA of tumorigenesis factors, oncogenes and anti-apoptotic factors have been identified as HuR targets (5).…”
Section: Introductionmentioning
confidence: 99%
“…14 HuR, in particular, can regulate hundreds of target transcripts and is considered to be a key regulator of many cellular functions, including proliferation, cellular stress response, and cell survival. 15 Indeed, HuR promotes the expression of general stress-response proteins (HSP70, HO-1, SOD1, p62) and hypoxia-response proteins, including HIF-1a and VEGFA. [16][17][18][19][20] Through its influence on subsets of cellular proteins, HuR has been linked to various pathologies, including inflammatory diseases and cancer.…”
Section: Introductionmentioning
confidence: 99%